Presenting of Coronavirus Anxiety Model based on Personality Traits, and Coping Strategies in Patients with COVID-19 - Safa, Mitra; Bazzazian, Saeideh; Ghassem Boroujerdi , Fatemeh; Aliabbasi, Fateme (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: The COVID 19 pandemic affected almost on all of the economic, political and social aspects of countries in the world. According to researches, anxiety and depression are common psychological reaction on the Coronavirus virus pandemic. The aim of this study was to investigate the moderating role of coping strategies in predicting of Coronavirus anxiety based on personality traits in patients with COVID-19. Materials and Methods: From all of the patients with COVID-19 referred to Masih Daneshvari Hospital, 120 patients (60 men, 60 women) were selected randomly. According to inferences criteria. Subjects complete Hexaco-PI-R, Coping Inventory for successful Situations (CISS), and Coronavirus Disease Anxiety Scale (CDAS). Data were analyzed using structural equation modeling. Results: The results of structural equation modeling showed that the direct effects of conscientiousness on problem-based coping strategies, and direct effects of emotionality and extraversion on emotion- based coping strategies were significant (P<0/05). Also, the direct effects of conscientiousness, emotionality and extraversion on and Coronavirus disease anxiety components were significant (P<0/05). Also, the goodness of fit indices for the hypothetical model had significant coefficients at P<0.05. Conclusions: Thus, results of the present study in addition to expanding the research literature, emphasis to the role of individual differences in predicting of Coronavirus disease anxiety and highlight the necessity of remarking these factors for designing appropriate interventions.